The modular synthesis of rare earth-transition metal heterobimetallic complexes utilizing a redox-active ligand. Issue 31 (13th June 2018) - Hickson, James R.; Horsewill, Samuel J.; Bamforth, Christopher; McGuire, Jake; Wilson, Claire; Sproules, Stephen; Farnaby, Joy H.
Abstract : The redox-active bridging ligand 1, 10-phenathroline-5, 6-dione, acts as the template for this modular synthetic route to f–d heterobimetallic complexes. Abstract : We report a robust and modular synthetic route to heterometallic rare earth-transition metal complexes. We have used the redox-active bridging ligand 1, 10-phenathroline-5, 6-dione (pd), which has selective N, N ′ or O, O ′ binding sites as the template for this synthetic route. The coordination complexes [Ln(hfac)3 ( N, N' -pd)] (Ln = Y [1 ], Gd [2 ]; hfac = hexafluoroacetylacetonate) were synthesised in high yield. These complexes have been fully characterised using a range of spectroscopic techniques. Solid state molecular structures of1 and2 have been determined by X-ray crystallography and display different pd binding modes in coordinating and non-coordinating solvents. Complexes1 and2 are unusually highly coloured in coordinating solvents, for example the vis-NIR spectrum of1 in acetonitrile displays an electronic transition centred at 587 nm with an extinction coefficient consistent with significant charge transfer. The reaction between1 and2 and VCp2 or VCp t 2 (Cp t = tetramethylcyclopentadienyl) resulted in the isolation of the heterobimetallic complexes, [Ln(hfac)3 ( N, N ′- O, O ′-pd)VCp2 ] (Ln = Y [3 ], Gd [4 ]) or [Ln(hfac)3 ( N, N ′- O, O ′-pd)VCp t 2 ] (Ln = Y [5 ], Gd [6 ]). The solid state molecular structures of3, 5 and6 have been determined by X-ray crystallography. The spectroscopic data on3–6 are consistent with oxidation of V(ii ) to V(iv ) and reduction of pd to pd 2− in the heterobimetallic complexes. The spin-Hamiltonian parameters from low temperature X-band EPR spectroscopy of3 and5 describe a 2 A1 ground state, with a V(iv ) centre. DFT calculations on3 are in good agreement with experimental data and confirm the SOMO as the d x 2 − y 2 orbital localised on vanadium.